2019
DOI: 10.3390/ph12040155
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of a HER2 Targeted Thorium-227 Conjugate in Combination with Olaparib in a BRCA2 Deficient Xenograft Model

Abstract: Targeted thorium-227 conjugates (TTCs) represent a novel class of therapeutic radiopharmaceuticals for the treatment of cancer. TTCs consist of the alpha particle emitter thorium-227 complexed to a 3,2-hydroxypyridinone chelator conjugated to a tumor-targeting monoclonal antibody. The high energy and short range of the alpha particles induce potent and selective anti-tumor activity driven by the induction of DNA damage in the target cell. Methods: The efficacy of human epidermal growth factor receptor 2 (HER2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…Importantly, the combination treatment appeared to be well tolerated. 84 These data support further investigation of the combinations of TTCs with specific DDR inhibitors in the BRCA2 -/setting.…”
Section: Rationale For Combining Ttcs With Inhibitors Of Ddrsupporting
confidence: 62%
See 2 more Smart Citations
“…Importantly, the combination treatment appeared to be well tolerated. 84 These data support further investigation of the combinations of TTCs with specific DDR inhibitors in the BRCA2 -/setting.…”
Section: Rationale For Combining Ttcs With Inhibitors Of Ddrsupporting
confidence: 62%
“…To test this hypothesis, several preclinical studies have been performed where TTCs were combined with DDR inhibitors. [84][85][86] A humanized HER2-targeting IgG1 antibody derived from trastuzumab was conjugated to the 3,2-HOPO chela-tor and subsequently radiolabeled with 227 Th resulting in HER2-TTC. 25 Robust tumor growth inhibition was achieved when HER2-TTC was combined at a subefficacious monotherapy dose of 125 kBq/kg with the poly-ADP ribose polymerase 1/2 (PARP1/2) inhibitor olaparib in the DLD-1 BRCA2 -/xenograft model established from the DLD-1 colorectal cancer cell line with inactivated BRCA2 gene, while no significant tumor inhibition occurred in the xenograft model established from the DLD-1 parental isogenic cell line (Table 2).…”
Section: Rationale For Combining Ttcs With Inhibitors Of Ddrmentioning
confidence: 99%
See 1 more Smart Citation
“…107 Synergistic efficacy has also been demonstrated with HER2 targeted 227 Th conjugates in combination with DNA repair inhibitor drug, olaparib (poly ADP ribose polymerase inhibitor) in BRCA2 deficient xenograft tumor models. 108 The same group of investigators have also reported on the potential utility of 227 Th conjugates targeting the fibroblast growth factor receptor 2 (FGFR2), which is overexpressed in many cancers, and in acute myeloid leukemia targeting CD33. 109,110 212 Pb…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Furthermore, MSLN targeting 227 Th conjugates have demonstrated synergistic antitumor effect when combined with DNA damage response inhibitors, particularly ATRi and PARPi in preclinical cancer models. 115 a Emitter Selection…”
mentioning
confidence: 99%